M. S. A. Rao, Urbanization and Social Change. A study of a Rural Community on a Metropolitan Fringe. Orient Longmans Ltd., Nueva Delhi, 1970. 254 pp. Mapas y Tablas. - S. D. (El Colegio de México, A.C., 1971)
-